Novel and recurrent COL11A1 and COL2A1 mutations in the Marshall-Stickler syndrome spectrum - (:unkn) unknown (NATURE PUBLISHING GROUP, 2017)
Marshall-Stickler syndrome represents a spectrum of inherited connective tissue disorders affecting the ocular, auditory, and skeletal systems. The syndrome is caused by mutations in the COL2A1, COL11A1, COL11A2, COL9A1, and COL9A2 genes. In this study, we examined four Turkish families with Marshall-Stickler syndrome using whole-exome sequencing and identified one COL2A1 mutation and three COL11A1 mutations. Two of the COL11A1 mutations were novel. Our findings expand our knowledge of the COL11A1 mutational spectrum that causes Marshall-Stickler syndrome.
Keywords: GENE; DYSPLASIA; DOMINANT; FAMILY